Exploring Anxiety Levels in Hypertensive Patients with Headache: A Cross-Sectional Study - Dhian Luluh Rohmawati (Jurnal Keperawatan Priority, 2026)
Hypertension is a chronic “silent killer” that affects over 1.4 billion people globally. Besides physical symptoms, hypertensive patients often experience anxiety, especially when accompanied by headaches. This study aimed to identify anxiety levels among hypertensive patients with headache and their implications for holistic nursing care. A descriptive quantitative study with a cross-sectional design was conducted at Puskesmas Ngawi Purba from February to May 2024. Forty-three hypertensive patients aged 35–55 years experiencing headaches were selected by accidental sampling. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS) and pain using the Numeric Rating Scale (NRS). Most respondents were female (69.8%), elderly (60.5%), and obese (44.2%). Moderate anxiety was found in 30.2% of participants, with 79.1% having stage 2 hypertension and 62.8% reporting moderate pain. Hypertensive patients with headache mostly experience moderate anxiety. Holistic nursing care addressing both physical and psychological aspects is essential to enhance blood pressure control and patient well-being.